SWOT Analysis of Forest Protected Area Based Sustainable Tourism Development: A Case Study in the Lawachara National Park, Bangladesh - Hossain, Mohammad Ismail; Khanal, Bishnu Prasad (Journal of Tourism and Hospitality Education, 2020)
Lawachara National Park (LNP) is one of the most important protected areas in the Sylhet region included in the blessed with the natural beauty of the forest and diverse wildlife of Northeast Bangladesh. This paper explores the possibility of sustainable forest tourism development in the study area regarding the sensible usage of the resource and local resident communities. To plan and properly implement this, various managements and decision-making tools were used, including interviews of local residents, visitors and the staff of the park, with the help of survey questionnaire (primary data) and secondary data acquired from Bangladesh Parjontan Corporation, conference proceedings, books, and journals. Based upon these data the strengths, weaknesses, opportunities, and threats (SWOT) were analyzed to identify the required management strategies to improve the sustainable forest protected area tourism in the hilly area. While introducing both domestic and international tourist attractions in the area, the influential factors in the region categorized into the four headings of strengths; weaknesses; opportunities and threats were included in our considerations and strategies or guidelines for a sustained eco tourism development in the region provided. The research findings, the well-established area forest tourism destination with a variety of natural attractions and unique culture of local people retaining ancient culture are the strengths of the area while lack of infrastructures and fundamental facilities are significant weaknesses. To maximize the internal strengths and external opportunities and to minimize internal weaknesses and external threats on the several strategies have been suggested for the sustainable forest protected area tourism development and management. However, there is a scope for the continuous improvement of the SWOT analysis in identifying more viable options for the strategic management of sustainable tourism.